Окремий корпус кордонної охорони (1918–1919 рр.) - Гай-Нижник, П. (Український історичний журнал, 2022)
Мета статті полягає у висвітленні процесу формування Окремого корпусу кордонної
охорони Української Народної Республіки та Української Держави впродовж 1918–1919 рр.
Методологія дослідження побудована на принципах історизму, об’єктивності, багатофакторності
й усебічного аналізу, а також на сучасному термінологічному апараті. Використано системний і
структурний методи. Наукова новизна. На підставі архівних, частина яких уперше вводиться в
науковий обіг, та опублікованих джерел проаналізовано організаційно-правові засади встановлення
інституту і структур державної кордонної служби в УНР та УД. Наведено статистичні дані стосовно
кількісного й територіального складів. Указано місця дислокації підрозділів, чисельність, керівні
органи, фінансування, функції, обов’язки, завдання. Зауважено на тісному співробітництві кордонної
охорони з митною службою та фінансовим відомством, урядових рішеннях щодо становлення та
діяльності Окремого корпусу кордонної охорони, його діяльності й комплектації. Наголошено на
ролі кордонної охорони як за умов мирного часу, так і в період війни. У висновках зазначено про
незавершеність процесу становлення кордонної охорони, її переформатування й перепідпорядкування
на етапі воєнних поразок та, зрештою, ліквідацію внаслідок краху української державності. The purpose of the article is to cover the process of formation of the Separate Corps
of Border Guards of Ukrainian People’s Republic and Ukrainian State during 1918–1919.
The research methodology is based on the principles of historicism, objectivity, multifactorial
and comprehensive analysis. System and structural methods are used. Scientific novelty. On
the basis of archival, some of which are introduced into scientific circulation for the first time,
and published sources, the organizational and legal principles of establishing the institute and
structures of the state border service in Ukrainian People’s Republic and Ukrainian State are
analyzed. Statistical data on the quantitative and territorial composition of the service are given.
The locations of border guards, its number, governing bodies, funding, functions, responsibilities,
tasks are indicated. It was noted on the close cooperation of the Border Guard with the Customs
Service and the Ministry of Finance of Ukraine, government decisions on the formation and
operation of the Separate Border Guard Corps, its activities and equipment. It is stated that
the policy of the Ukrainian State (as well as the Ukrainian People’s Republic) in the field of legal
and administrative arrangement and functioning of border guards was temporarily based on the
all-Russian legal framework, which was adjusted by current laws, decrees, circulars and orders of
Ukrainian governments and new political and economic agreements. state Ukraine with other
countries, which was concluded during 1918 as full representatives of Ukrainian People’s Republic
and Ukrainian State. The role of border guards was emphasized both in peacetime and during
hostilities. The conclusions indicate that the main tasks of the Separate Corps of Border Guards
were determined: the organization of border protection by setting up special posts; control over the
movement of persons across the border in the presence of relevant documents and counteraction
to illegal import (export) of goods, weapons, ammunition, etc.; detention of deserters and criminal
elements; performing quarantine and police services at the border. Also, units of the Separate
Border Guard Corps were to bear paramilitary responsibility for border security, working closely
with the customs offices of the Department of Customs Duties of the Ministry of Finance and the
Department of Border Care of the Ministry of Trade and Industry to protect Ukrainian industry
and protect the interests of the treasury. Emphasis was placed on the incompleteness of the process
of formation of the border guard, its reformatting and re-subordination during the period of
military failures and, finally, liquidation due to the collapse of Ukrainian statehood.